Time‐dependent evolution of functional vs. remodeling signaling in induced pluripotent stem cell‐derived cardiomyocytes and induced maturation with biomechanical stimulation. Issue 4 (16th December 2015) - Jung, Gwanghyun; Fajardo, Giovanni; Ribeiro, Alexandre J. S.; Kooiker, Kristina Bezold; Coronado, Michael; Zhao, Mingming; Hu, Dong‐Qing; Reddy, Sushma; Kodo, Kazuki; Sriram, Krishna; Insel, Paul A.; Wu, Joseph C.; et al.
Abstract : Human induced pluripotent stem cell‐derived cardiomyocytes (hiPSC‐CMs) are a powerful platform for uncovering disease mechanisms and assessing drugs for efficacy/toxicity. However, the accuracy with which hiPSC‐CMs recapitulate the contractile and remodeling signaling of adult cardiomyocytes is not fully known. We used β‐adrenergic receptor (β‐AR) signaling as a prototype to determine the evolution of signaling component expression and function during hiPSC‐CM maturation. In "early" hiPSC‐CMs (less than or equal to d 30), β2‐ARs are a primary source of cAMP/PKA signaling. With longer culture, β1‐AR signaling increases: from 0% of cAMP generation at d 30 to 56.8 ± 6.6% by d 60. PKA signaling shows a similar increase: 15.7 ± 5.2% (d30), 49.8 ± 0.5% (d 60), and 71.0 ± 6.1% (d 90). cAMP generation increases 9‐fold from d 30 to 60, with enhanced coupling to remodeling pathways ( e.g., Akt and Ca 2+ /calmodulin‐dependent protein kinase type II) and development of caveolin‐mediated signaling compartmentalization. By contrast, cardiotoxicity induced by chronic β‐AR stimulation, a major component of heart failure, develops much later: 5% cell death at d 30 vs. 55% at d 90. Moreover, β‐AR maturation can be accelerated by biomechanical stimulation. The differential maturation of β‐AR functional vs. remodeling signaling in hiPSC‐CMs has important implications for their use in disease modeling and drug testing. We propose that assessment of signaling be added to the indices of phenotypic maturation of hiPSC‐CMs.—Jung, G., Fajardo, G., Ribeiro, A. J. S., Kooiker, K. B., Coronado, M., Zhao, M., Hu, D.‐Q., Reddy, S., Kodo, K., Sriram, K., Insel, P. A., Wu, J. C., Pruitt, B. L., Bernstein, D. Time‐dependent evolution of functional vs. remodeling signaling in induced pluripotent stem cell‐derived cardiomyocytes and induced maturation with biomechanical stimulation. FASEB J. 30, 1464–1479 (2016). www.fasebj.org